Implementation of Religious Moderation in Strengthening Unity and Harmony Between Religious Communities - Didik Himmawan; Dewinta Silviyana; Fitri Nashifa; Dwi Rika Wahyuni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to describe religious moderation for religious communities. The research method used is literature study. This research concludes that radicalism in the name of religion can be eradicated through moderate and inclusive Islamic education. Religious moderation can be demonstrated through sıkan tawazun (balanced). Ltidal (straight and firm), tasamuh (tolerant), musawah (egalitarian), shura (deliberation), ishlah (reformation), aulawiyah (putting priorities first), tathawwut wa ibtikar (dynamus and innovative). with inherent diversity. Diversity, which includes various differences such as culture and race. religion, ethnicity, language, traditions and others. With so many differences, it is possible that conflict will arise. So the strategy for dealing with this diversity is religious moderation using the benefits of a harmonious, peaceful & tolerant religious & national life for the Maru Indonesian nation. Religious moderation As a multicultural and multicultural country, conflicts with religious backgrounds may arise. This means that religious communities cannot be harmonious and conflicts continue to arise. Because of this conflict, religious moderation can strengthen harmony between religious communities because religious moderation is needed as a solution because it is an important key to creating social, state and religious life.